Effectiveness of Multi-Dimensional Spiritual-Religious Psychotherapy on Mental Distress and Resilience of Addicted Women under Remedy - Javdan, Moosa; Sharafi, Najme; Foroozanfar, Aabdollah; Javdan, Anahita (Psychology of Woman Journal, 2023)
Objective: Insufficient supervision of children by families and lack of care and guidance in leisure and unemployment, lack of healthy equipment and recreation and sports and lack of proper education, lack of superficial knowledge of people about the dangers of drugs, lack of love, nervous pain, discomfort Physically, failures are important causes of addiction. Method: This study aimed to evaluate the effectiveness of multidimensional spiritual-religious psychotherapy on mental distress and resilience of addicted women under remedy in Bandar Abbas City. This study’s design was quasi-experimental as a pre-test-post-test with the control group. The statistical population consisted of all addicted women under remedy in Bandar Abbas City in 2019. The study sample consisted of 29 women (14 individuals in the experimental group and 15 individuals in the control group) randomly selected from women referred to counseling centers in Bandar Abbas and randomly assigned to experimental and control groups members of the experimental group underwent multidimensional spiritual-religious psychotherapy. The Data were collected using Depression, Anxiety, and Stress Scale (DASS), and Resilience Scale (CD-RISC). Data Analyzing was conducted with one-way MANCOVA and SPSS-22. Results: The results showed that there is a significant difference between the experimental and control groups in mental distress (F= 12/50, p< 0.05) and resiliency (F= 4.61, p< 0.05). Conclusion: According to the findings of this study, multidimensional spiritual-religious psychotherapy is an effective method in improving the mental disorder and resilience of addicted women under treatment. It can be recognized as one of the effective variables in psychotherapy.